THE INFLUINCE OF ONLINE CUSTOMER RIVIEW AND ONLINE CUSTOMER RATING ON PURCHASE DECISIONS THROUGH SHOPEE (Study On Students Of Faculty Of Economics, Universitas Islam Lamongan) - Ajeng Septianing Tyas; Titin Titin; Kemal Farouq Mauladi (Sean Institute, 2022)
The purpose of this research is to find out whether Online Customer Rating (X1), Online Customer Rating (X2) and purchasing decisions (Y) in the study shopee application for students of the economics faculty of the Universitas Islam Lamongan. The test results show that: T test of variable Online Customer Riview (5.727) > Ttable (0.131), Online Customer Rating variable obtained Tcount (3.061) > Ttable (0.131). ),Uji F hitung (197,647) > Ftabel (2,65). From the multiple linear regression test Y = 4.224 + 0.348 + 0.183 + 0.362, it can be seen that the most dominant value is Online Customer Riview of 0.362.